Silicon Photonic Modulators for Low-power Applications - Palmer, Robert (Karlsruhe Series in Photonics and Communications / Karlsruhe Institute of Technology, Institute of Photonics and Quantum Electronics (IPQ), 2015)
In this book, silicon photonic integrated circuits are combined with electro-optic organic materials for realizing energy-efficient modulators with unprecedented performance. These silicon-organic hybrid Mach-Zehnder modulators feature a compact size, sub-Volt drive voltages, and they support data rates up to 84 Gbit/s. In addition, a wet chemical waveguide fabrication scheme and an efficient fiber-chip coupling scheme are presented.